A universal primer-independent next-generation sequencing approach for investigations of norovirus outbreaks and novel variants - Fonager, Jannik (Sci Rep, 2017)
Norovirus (NoV) is the most common cause of non-bacterial gastroenteritis and is a major agent associated with outbreaks of gastroenteritis. Conventional molecular genotyping analysis of NoV, used for the identification of transmission routes, relies on standard typing methods (STM) by Sanger-sequencing of only a limited part of the NoV genome, which could lead to wrong conclusions. Here, we combined a NoV capture method with next generation sequencing (NGS), which increased the proportion of norovirus reads by ~40 fold compared to NGS without prior capture. Of 15 NoV samples from 6 single-genotype outbreaks, near full-genome coverage (>90%) was obtained from 9 samples. Fourteen polymerase (RdRp) and 15 capsid (cap) genotypes were identified compared to 12 and 13 for the STM, respectively. Analysis of 9 samples from two mixed-genotype outbreaks identified 6 RdRp and 6 cap genotypes (two at >90% NoV genome coverage) compared to 4 and 2 for the STM, respectively. Furthermore, complete or partial sequences from the P2 hypervariable region were obtained from 7 of 8 outbreaks and a new NoV recombinant was identified. This approach could therefore strengthen outbreak investigations and could be applied to other important viruses in stool samples such as hepatitis A and enterovirus.